THE IMPACT OF DUOLINGO APPLICATION ON STUDENTS’ ENGLISH COMPETENCE - Faradea, Jessyka Chandra; Maghfiroh, Ana; Laksana, Sigit Dwi; Sugianto, Alip (Universitas Muhammadiyah Ponorogo, 2025)
This research investigates the impact of Duolingo's app on students' language ability in learning English. This research aims to 1) the ease of use duolingo application, 2) The benefits we get from the features provided by the Duolingo application, 3) Identify what improvements are visible in English competence. This research is a qualitative study to identify the impact of Duolingo application on student’s English competence. Participants were two high school students and two college students who currently use Duolingo regularly. The researchers conducted structured interviews to obtain rich details about their experiences. The findings suggested that Duolingo's usability, engaging features and systematic lessons has significantly contributed to their language learning ability, especially in terms of pronunciation, vocabulary and their confidence in using English. This research also emphasized the educational value of such an innovation in a digital era.